2016
DOI: 10.4103/2303-9027.183979
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of electromagnetic navigation bronchoscopy with or without radial endobronchial ultrasound for peripheral lung lesions

Abstract: Background and Objectives:Electromagnetic navigation bronchoscopy (ENB) is a promising new technology to increase the diagnostic yield of peripheral lung and mediastinal lesions. Conventional flexible bronchoscopy has a limited yield in peripheral pulmonary lesions, even in experienced hands. Radial endobronchial ultrasound (r-EBUS) with its real-time imaging capability can help to diagnose peripheral pulmonary lesions. In the present study, we aimed to investigate the diagnostic yield and safety of ENB with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…The median duration of the procedure was 57 min overall and 31 min for the ENB procedure, similar to the overall NAVIGATE study (52 min and 25 min, respectively) 22 and ENB literature reports ranging from 20 to 70 min. 31,32 Procedure times were even shorter in those patients with only FM placement and no lung lesion biopsy. Additionally, ENB guidance was aided by cone–beam CT in 4% and rEBUS in 37%.…”
Section: Discussionmentioning
confidence: 96%
“…The median duration of the procedure was 57 min overall and 31 min for the ENB procedure, similar to the overall NAVIGATE study (52 min and 25 min, respectively) 22 and ENB literature reports ranging from 20 to 70 min. 31,32 Procedure times were even shorter in those patients with only FM placement and no lung lesion biopsy. Additionally, ENB guidance was aided by cone–beam CT in 4% and rEBUS in 37%.…”
Section: Discussionmentioning
confidence: 96%
“…Very few studies analyzing the correlation between the density of lesion and diagnostic yield. [ 20 ] A recent prospective multicenter clinical study showed that the diagnostic yield of ENB was 72.9% and the false negative rate was 45.4% after 1-year follow-up completed. [ 21 ] However, in this high credibility study only 6.3% of the enrolled cases were SSNs, and the diagnostic yield subgroup analysis of SN and SSN were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to R-EBUS, promising techniques for interventional bronchoscopy of peripheral lung lesions include ENB27 and VB728. The reported diagnostic performance was 74% with ENB4 and about 80% with VB2930 and the combination of these modalities achieved success rate of 80%–81% (R-EBUS and VB)531 and 63%–73% (R-EBUS and ENB)3233. There was no clear indication for these tools, thus the comparisons and combinations to establish proper use are still required.…”
Section: Discussionmentioning
confidence: 99%